Identification of geological units in Alborz Mountain in Iran using Landsat-9 image - Rokni, Komeil; Akbari, Davood (Geodesy and Cartography, 2024)
In the present study, the suitability of principal components analysis (PCA) based techniques was evaluated for identification of geological units from Landsat-9 satellite imagery. In this respect, a scene of Landsat-9 operational land imager 2 (OLI–2) data of the year 2023 was acquired and a geological map scale 1:100000 of the study area was used as the reference. The results indicated suitability of the PCA based techniques for discrimination of geological units from Landsat-9 image, especially the PCA of decorrelation stretch (DS) approach. The PCA-DS approach, which considered the advantages of both PCA and DS techniques, successfully identified all the geological units in the study area, including the Basalt, Sandstone, Dolomite, and Conglomerate. However, the performance of the PCA and DS techniques was also reasonable for this purpose. On the other hand, the study revealed weak performance of the minimum noise fraction (MNF) and PCA-MNF techniques for geological mapping using Landsat-9 imagery. In conclusion, the study demonstrated the advantage of the PCA-DS approach for geological mapping using Landsat-9 imagery; therefore, it may be useful in futures studies for geological mapping along the whole Alborz Mountain with similar lithological and geomorphological conditions.